East Asian Monsoon as a Modulator of U.S. Great Plains Heat Waves. Issue 12 (24th June 2019) - Lopez, Hosmay; Lee, Sang‐Ki; Dong, Shenfu; Goni, Gustavo; Kirtman, Ben; Atlas, Robert; Kumar, Arun
Abstract: Heat waves are the leading weather‐related cause of death in the United States, with the most recent examples occurring in the summers of 2011 and 2012 over the Great Plains. These events are unusual and largely unpredictable beyond the synoptic timescale. Their number and severity have increased and are projected to continue to increase, prompting the need to identify the physical processes that modulate heat waves and, consequently, can lead to improved prediction and future projection. Our results based on observations and model simulations suggest that convective latent heat release from the East Asian Monsoon enhances the likelihood of droughts and heat waves over the United States through an equivalent barotropic wave train along the subtropical jet stream, promoting an anticyclonic circulation pattern over the Great Plains. This anticyclone serves as a blocking pattern for transient synoptic‐scale systems and is supportive of persistent drought and clear sky conditions, promoting high temperatures and heat waves. Key Points: The influence of the East Asian Monsoon (EAM) on the summer climate of the Great Plains of the United States is investigated The EAM forces an upper‐level ridge over the Great Plains of the United States, increasing temperature and drought over that region in boreal summer The amplitude and frequency of occurrence of heat waves increases as a result of the reduced precipitation and stagnant circulation